Public attitude and media governance of biometric information dissemination in the era of digital intelligence - Wenyi Zhang; Hengtian Zhang; Zhouyang Deng (Scientific Reports)
Abstract Absrtact: In the era of digital intelligence, biometrics plays a critical role in mediating sensitive information dissemination, human-computer interaction, and governance in both virtual and real-world settings, including the evolving metaverse. Based on an empirical analysis of 1,862 participants, the current study investigated factors influencing public perception, acceptance, and risk awareness of biometric technologies. The findings highlight the critical roles of perceived trust (PT) and technical prudence (TP) in driving behavioral intentions (BI), with their positive effects outweighing the significant deterrent impact of perceived risks (PR). While PT and perceived availability (PA) significantly enhance the adoption of biometric technologies, TP exhibited an unexpected positive influence, suggesting that cautious users may still embrace biometrics if perceived as secure and trustworthy. These results emphasize the urgency of refining legal and regulatory frameworks, improving risk mitigation strategies, and enhancing user confidence to foster the responsible adoption and utilization of biometric technologies. This study offers valuable insights into the interplay of factors such as perceived trust, risks, and technological prudence in shaping behavioral intentions, contributing to a deeper understanding of biometrics in a rapidly digitizing society.